An Independent 1D Single‐Walled Metal–Organic Nanotube Transformed from a 2D Layer Exhibits Highly Selective and Reversible Sensing of Nitroaromatic Compounds. Issue 17 (19th March 2014) - Zhang, Qingfu; Geng, Aijing; Zhang, Haina; Hu, Falu; Lu, Zhang‐Hui; Sun, Dezhi; Wei, Xilian; Ma, Chunlin
Abstract The syntheses and structures of two new ZnII complexes, a 2D graphite‐like layer [Zn(PIA)H2O]⋅H2On (1) and an independent 1D single‐walled metal–organic nanotube (SWMONT) [Zn2(PIA)2(bpy)2]⋅2.5 H2O⋅DMAn (2), have been reported based on a "Y"‐shaped 5‐(pyridine‐4‐yl)isophthalic acid ligand (H2PIA). Interestingly, the 2D graphite‐like layer in 1 can transform into the independent 1D SWMONT in 2 with addition of 2, 2′‐bipyridine (bpy), which represents the first successfully experimental example of an independent 1D metal–organic nanotube generated from a 2D layer by a "rolling‐up" mechanism.